2013
DOI: 10.1158/1535-7163.mct-13-0151
|View full text |Cite
|
Sign up to set email alerts
|

The Novel ATP-Competitive Inhibitor of the MET Hepatocyte Growth Factor Receptor EMD1214063 Displays Inhibitory Activity against Selected MET-Mutated Variants

Abstract: The receptor tyrosine kinase MET is a prime target in clinical oncology due to its aberrant activation and involvement in the pathogenesis of a broad spectrum of malignancies. Similar to other targeted kinases, primary and secondary mutations seem to represent an important resistance mechanism to MET inhibitors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…In contrast, SAR125844 was inactive on cell lines expressing D1228H and Y1230H mutants, despite biochemical activity of 81 and 204 nmol/L, respectively, suggesting that an affinity of 50 nmol/L or lower is necessary to translate into significant MET inhibition in cell lines. Overall, the activity of SAR125844 on these selected MET mutants is equivalent to the one observed with EMD1214063 (47), and suggests that highly selective type I MET inhibitors might not be active on MET mutants such as Y1230H or D1228H compared with type II nonselective MET inhibitors. Interestingly, in contrast to somatic mutations, germline MET mutations were highly predictive of a response to foretinib in patients with papillary renal cell carcinoma (48).…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, SAR125844 was inactive on cell lines expressing D1228H and Y1230H mutants, despite biochemical activity of 81 and 204 nmol/L, respectively, suggesting that an affinity of 50 nmol/L or lower is necessary to translate into significant MET inhibition in cell lines. Overall, the activity of SAR125844 on these selected MET mutants is equivalent to the one observed with EMD1214063 (47), and suggests that highly selective type I MET inhibitors might not be active on MET mutants such as Y1230H or D1228H compared with type II nonselective MET inhibitors. Interestingly, in contrast to somatic mutations, germline MET mutations were highly predictive of a response to foretinib in patients with papillary renal cell carcinoma (48).…”
Section: Discussionmentioning
confidence: 83%
“…We observe this phenomenon, surprisingly not previously reported, both in cells overexpressing the wt MET (human non-small cell lung cancer line H1993) as well as in NIH3T3 cells expressing activating MET mutated variants that overall respond to MET inhibition (MET H1112L, M1268T, V1110I, and V1238I mutations). Contrary, NIH3T3 MET L1213V and NIH3T3 MET Y1248H mutants, that have been previously shown to be resistant to MET small molecule inhibitors [22,23,26], do not respond to MET inhibition by decrease in tyrosine autophosphorylation and also do not display the increase in total MET protein upon treatment with any of the currently used MET inhibitors (Fig. 1).…”
Section: Met Inhibition By Small Molecule Tkis Increases Total Cellulmentioning
confidence: 94%
“…These results indicate that MET kinase domain mutations may be a mechanism to circumvent MET TKI inhibition. Several earlier studies have demonstrated the ability of MET kinase domain mutations to diminish the efficacy of MET inhibitors (44)(45)(46). It is likely that additional and novel mutations will be identified with the emergence of genomic profiling of recurrent disease through biopsies, circulating tumor cells, and circulating DNA.…”
Section: Reemergence Of Met Kinase Domain Mutations During Resistancementioning
confidence: 99%